Approach Management In Marine Protected Areas : A Case Study of Surin Marine National Park, Thailand - Sucai Worachananant; Sara Shamshiri; Gilbert Ryan Semilla (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Research This aiming For identify limiting factors​ effectiveness of management strategies area conservation the sea in Thailand, as well as to study how are those strategies can improved , through studies the case of Surin Marine National Park. Methodology: The method used covering studies literature , survey social towards stakeholders​ interests ( visitors , tour operators, staff) park national ), as well as survey biological use line intercept transect technique . Post-tsunami data from 2004 were also collected For evaluate change condition ecology and capacity management Main Findings: Research results show that approach management in Surin yet fully effective in guard sustainability environment sea . Conflict between stakeholders interests , weakness capacity management , and change condition post tsunami become challenge main . Management based on zoning Still need revision and participation more wide . Novelty/Originality of this study: This study integrate perspective biological and sociological as well as evaluate impact crisis big (2004 tsunami) against effectiveness management area conservation. Approach This produce framework contextual and accessible evaluation​ applied in management area sea similar in developing countries.